Features of Operation of a Brightness Amplifier on Copper Bromide Vapors in the Bistatic Scheme of a Laser Monitor; Atmospheric and Oceanic Optics; Vol. 32, iss. 4 - Vasnev N. A. Nikolay Aleksandrovich (2019, 2019)
Title screen